The weekend crashers - Brenner, Jamie, 1971- (Park Row, 2025)
A knitting retreat gets knotty in this humorous and poignant novel about love, second chances, and the unyielding bonds between mothers and daughters. Maggie Hodges and her daughter Piper are looking forward to a restful knitting retreat in the picturesque village of New Hope, Pennsylvania. But instead, they are surprised to find themselves sharing their charming riverside inn with a rowdy bushcraft bachelor party. Undaunted by the clash of interests and personalities, Maggie suggests a lighthearted competition--a battle of crafts--that sparks a rivalry between the two groups, and perhaps something more. But as the weekend unfolds, old mistakes and buried resentments begin to surface, threatening to destroy Maggie and Piper's cherished connection.In knitting, one can easily fix mistakes by picking apart each stitch and starting anew. But life's tangles aren't so easily mended. With tensions rising and the retreat coming to a close, Maggie must act quickly before she loses everything she holds dear. Can she repair what's been broken before everything unravels?